Probability and statistics for engineering and the sciences / Jay L Devore - Devore, Jay L
Offers a comprehensive introduction to probability and statistics. Through the use of examples, this book helps you in putting the statistical methods to use. It emphasizes concepts, models, methodology, and applications that aim to facilitate your understanding.